(untitled) (Encuentros, 2021)
This paper presents the results obtained in the analysis of the right to petition (RP) as a textual genre that promotes the recognition of rights in a university institution in Antioquia (Colombia) in 2019. This research was qualitative, hermeneutical-comprehensive. The unit of analysis collected was made up of 46 RP corresponding to all of the RP filed, three interviews with officials of said institution and a focus group made up of four petitioners. From the analysis, it was concluded that the RP has different structures, which vary depending on the petitioner, ranging from the disciplinary to the merely enunciative, with its function predominant in the citizen participation of the public administration.